1988
DOI: 10.1090/s0002-9947-1988-0946440-2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-orbit shadowing in the family of tent maps

Abstract: ABSTRACT. We study the family of tent maps-continuous, unimodal, piecewise linear maps of the interval with slopes ±s, \/2 < s < 2. We show that tent maps have the shadowing property (every pseudo-orbit can be approximated by an actual orbit) for almost all parameters s, although they fail to have the shadowing property for an uncountable, dense set of parameters.We also show that for any tent map, every pseudo-orbit can be approximated by an actual orbit of a tent map with a perhaps slightly larger slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 2 publications
1
56
1
1
Order By: Relevance
“…Moreover, it may be seen that is a non-wandering dynamical system with shadowing. A particular example here is the full tent map f (x) = 1 − |1 − 2x| or various other maps from the family of tent maps [15].…”
Section: Theorem 54 Let (X F ) Be a Non-wandering And Topologicallymentioning
confidence: 99%
“…Moreover, it may be seen that is a non-wandering dynamical system with shadowing. A particular example here is the full tent map f (x) = 1 − |1 − 2x| or various other maps from the family of tent maps [15].…”
Section: Theorem 54 Let (X F ) Be a Non-wandering And Topologicallymentioning
confidence: 99%
“…Furthermore, they have been the subject of many research articles [12,17,28,30], often in relation to their ω-limit sets [6,21,22,23,24]. In this paper we make several important observations about the behaviour of tent maps, allowing us to prove new results about the nature of their limit sets in relation to certain well-known dynamical properties.…”
Section: Introductionmentioning
confidence: 95%
“…These maps do not have shadowing as the critical point is not recurrent [17]. Thus we suggest the following revision of Conjecture 1.1: We believe that this conjecture would be of interest, despite the fact that we know it holds for limit shadowing rather than shadowing, because the two properties are not equivalent [29], and shadowing is simple to test for [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if the above example lies on a space M 1 , and on another space M 2 there is a hyperbolic attractor, then the attractor for the product system is chaotic and has the shadowing property, but the attractor is not hyperbolic. For a simpler example, Coven, Kan and Yorke [9] have shown that tent maps are shadowable for all parameter values (i.e. , the absolute value of the slopes) between 1 and 2 except for a set having zero Lebesgue measure.…”
Section: Introductionmentioning
confidence: 99%